Evaluating Medical Student Communication/Professionalism Skills from a Patient’s Perspective - Davis, Larry E.; King, Molly K.; Wayne, Sharon J.; Kalishman, Summers G. (Frontiers in Neurology, 2012)
Objective: Evaluate medical student's communication and professionalism skills from the perspective of the ambulatory patient and later compare these skills in their first year of residency. Methods: Students in third year neurology clerkship clinics see patients alone followed by a revisit with an attending neurologist. The patient is then asked to complete a voluntary, anonymous, Likert scale questionnaire rating the student on friendliness, listening to the patient, respecting the patient, using understandable language, and grooming. For students who had completed one year of residency these professionalism ratings were compared with those from their residency director. Results: Seven hundred forty-two questionnaires for 165 clerkship students from 2007 to 2009 were analyzed. Eighty-three percent of forms were returned with an average of 5 per student. In 64% of questionnaires, patients rated students very good in all five categories; in 35% patients selected either very good or good ratings; and <1% rated any student fair. No students were rated poor or very poor. Sixty-two percent of patients wrote complimentary comments about the students. From the Class of 2008, 52% of students received "better than their peers” professionalism ratings from their PGY1 residency directors and only one student was rated "below their peers". Conclusions: This questionnaire allowed patient perceptions of their students' communication/professionalism skills to be evaluated in a systematic manner. Residency director ratings of professionalism of the same students at the end of their first year of residency confirms continued professional behavior.